PREVALENCE OF METHICILLIN-RESISTANT Staphylococcus aureus COLONIZATION AMONG HOSPITAL PATIENTS OF TEBESSA REGION IN EAST ALGERIA (Applied Biological Research, 2023)
Staphylococcus aureus is a human pathogen of clinical importance related to  a variety of infections. The objective of this study was to analyze theepidemiological characteristics of S. aureus obtained from the patients of  several hospitalin Tebessa area (East Algeria). This study was made as per the microbiological methods based on morpho-physio-biochemical  characters. S. aureus samples (1200) were analyzed, and 250 strains were  identified, representing the 20.83% of population. An antibiogram  accompanied by screening on oxacillin (6 μg mL-1) made it possible to detect  β-lactam resistant strains. Seventy eight (31.2%) methicillin-resistant  Staphylococcus aureus (MRSA) strains were isolated. The study revealed  that the risk factors like age, nature of sampling and use of β-lactams  antibiotics by patients have a relationship with MRSA infection. On the  other hand, the presence of MRSA has no relationship with sex factor of  hospitalized patients. By comparison with previous studies, it is inferred that  in Algeria the carriage of MRSA in the city is worrying. It is necessary to  control the diffusion of these strains for the control of epidemics with multi resistant germs.
Keywords: Algeria; antibiogram; epidemiology; methicillin-resistant strains; Staphylococcus aureus